Moving Applications to the Cloud (3rd Edition) - Betts, Dominic (Microsoft, 2015)
How can a company’s applications be scalable and have high availability? To achieve this, along with developing the applications, you must also have an infrastructure that can support them. For example, you may need to add servers or increase the capacities of existing ones, have redundant hardware, add logic to the application to handle distributed computing, and add mechanisms to handle failover. You have to do this even if an application is in high demand for only short periods of time. Life becomes even more complicated (and expensive) when you start to consider issues such as network latency and security boundaries...